2018
DOI: 10.1177/2167702618766290
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Adjustment Disorder Following Involuntary Job Loss and Its Predictors of Latent Change

Abstract: Adjustment disorders (AjDs) usually resolve after the precipitating life event and its consequences are terminated. However, they bear the risk for the development of severe mental illness. The present study investigates the natural course of AjD as defined for International Classification of Diseases, 11th version (ICD-11). A total of 303 individuals who involuntarily lost their jobs were assessed initially after the job loss and 6 months later. Latent class latent change analysis and multinomial logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
7
20
0
1
Order By: Relevance
“…Adjustment disorder was also associated with exposure to stressors, particularly those related to employment and health. Our findings are largely in line with other studies that found female gender and elderly age were associated with higher rates of adjustment disorder symptoms (Ayuso-Mateos et al, 2001;Lorenz et al, 2018b). Surprisingly, university education was also found to be a risk factor for adjustment disorder, even though higher education is often considered to be a protective factor for mental disorders.…”
Section: Predictors Of Adjustment Disordersupporting
confidence: 92%
See 3 more Smart Citations
“…Adjustment disorder was also associated with exposure to stressors, particularly those related to employment and health. Our findings are largely in line with other studies that found female gender and elderly age were associated with higher rates of adjustment disorder symptoms (Ayuso-Mateos et al, 2001;Lorenz et al, 2018b). Surprisingly, university education was also found to be a risk factor for adjustment disorder, even though higher education is often considered to be a protective factor for mental disorders.…”
Section: Predictors Of Adjustment Disordersupporting
confidence: 92%
“…Our study is in line with other studies that found that job-related stressors, such as higher responsibilities or occupational demanding work positions were associated with ICD-11 adjustment disorder symptoms (Perkonigg et al, 2018). Unemployment in our study was not associated with adjustment disorder in contrast to previous studies that identified high adjustment disorder prevalence associated with job loss (Lorenz et al, 2018b). Exposure to life-stressors, job-or health-related stressors, was significantly associated with ICD-11 adjustment disorder.…”
Section: Predictors Of Adjustment Disordersupporting
confidence: 90%
See 2 more Smart Citations
“…It can be assigned some days after the stressor has impacted on the person, and it is typically expected to resolve within 6 months unless the stressor persists for a longer duration. Adjustment disorder is not a trivial conditionif it goes undetected and untreated it may lead to more severe mental disorders or an elevated risk of suicide [67,68]. The four diagnoses presented here are intended to fulfill the aim of the ICD-11 to provide clear, simple diagnoses that meet the needs of clinicians worldwide.…”
Section: Adjustment Disordermentioning
confidence: 99%